Effectiveness of Benralizumab in Improving the Quality of Life of Severe Eosinophilic Asthmatic Patients: Our Real-Life Experience - Scioscia, Giulia; Carpagnano, Giovanna Elisiana; Quarato, Carla Maria Irene; Lacedonia, Donato; Santamaria, Sonia; Soccio, Piera; Depalo, Annarita; Fuso, Paolo; Foschino Barbaro, Maria Pia (Frontiers in Pharmacology, 2021)
Background: Severe eosinophilic asthma decreases lung function and causes worsen symptoms, often forcing recurrent maintenance corticosteroid use. The aim of our real-life study was to evaluate the effectiveness of an add-on treatment with benralizumab in patients with severe eosinophilic asthma, paying particular attention to the impact on their quality of life (QoL). Materials and methods: In this prospective study, 10 outpatients with severe eosinophilic asthma were added-on with benralizumab and followed-up in our severe asthma clinic after 12 and 24 weeks. At each patient visit, pre-bronchodilator FEV1 and inflammatory markers were recorded. Variations in asthma symptoms control and QoL perception was assessed by validated questionnaires. Results: All the subjects experienced a marked reduction of nocturnal and diurnal symptoms over time and were able to stop using OCS, as documented by the improvement in ACT and ACQ score. Similarly, we recorded a statistically significant increase in patient's QoL perception in EQ-VAS, EQ-5D-3L and AQLQ assessment (p<0.05). Simultaneously we recorded a significant reduction in eosinophilic inflammation, an improvement in pre-bronchodilator FEV1. These results appear to be in line with those already obtained in the previous randomized controlled trials (RCTs). Conclusion: Our 24-week real life experience supports the effectiveness of an add-on treatment with benralizumab in reducing eosinophilic inflammation and OCS-use, increasing lung function and improving control of nocturnal and diurnal symptoms, as well as restoring severe asthma patients to a better QoL.